Al-Qatt Al-Asiri Art as an Experimental approach to produce a contemporary sculpture works based on the light art - Alhedaithy, Haifa Ali (Journal of Humanities & Social Sciences, 2022)
The study aimed to identify the art of Al-Qatt Al-Asiri, identify the concept of contemporary sculpture, and clarify the art of light, in addition to employing the art of Al-Qatt Al-Asiri as an experimental approach to the production of contemporary sculptural works based on the art of light. To achieve this, the descriptive analytical method was used, by addressing the art of Al-Qatt Al-Asiri, contemporary sculpture, and the art of light. And also, the use of the experimental method in the study through the researcher’s implementation of a number of contemporary sculptural works inspired by the structural basics of Al-Qatt Al-Asiri art using the light technology in its various forms, which helps to verify the hypothesis of the research. The study reached many results, namely that the structural factors of Al-Qatt Al-Asiri’s art showed flexibility in adapting its vocabulary by creating light sculptural models in a way that matches the data of the times. The majority of Al-Qatt Al-Asiri’s sculptural designs relied on abstraction as an essential element to show the contemporary aesthetic side. The field of contemporary sculptural works preserves the creative content of the artwork in the diversity of its plastic formulations, without adhering to the traditional concept of sculpture. And also, to identify the characteristics of the art of light and its concept as one of the contemporary artistic trends related to technology. As light has an important role in emphasizing the importance of the technological techniques used in the production of sculptural works and making formal changes to them. In addition to the possibility of employing Al-Qatt Al-Asiri art as an experimental approach to the production of contemporary sculptural works based on the art of light. The study reached several recommendations, represented in conducting more studies on the art of Al-Qatt Al-Asiri. To show its aesthetics and preserve it from extinction. Interest in studying contemporary artistic trends, and raising awareness of them. And also, the establishment of a virtual museum to document the contemporary Saudi heritage and the possibility of reaching the largest possible number of audiences and disseminating it around the world.